2020
DOI: 10.13057/biodiv/d210535
|View full text |Cite
|
Sign up to set email alerts
|

Abundance of ants (Hymenoptera: Formicidae) and the functional groups in two different habitats

Abstract: Abstract. Triyogo A, Budiadi, Widyastuti SM, Subrata SA, Budi SS. 2020. Abundance of ants (Hymenoptera: Formicidae) and the functional groups in two different habitats. Biodiversitas 21: 2079-2087. Land development often affects the quantity and diversity of ants (Hymenoptera: Formicidae). The aim of this study, therefore, was to determine and compare the ant species abundance and the functional groups between two different habitats, representing land development, including pioneer and agroforestry. This resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 58 publications
2
26
0
Order By: Relevance
“…Formicidae families are the most common group of insects found on agricultural and croplands. Ecosystem habitat in this research presented the former condition of that land as increasing quality, which was dominated by a predator as the Formicidae, and also the ones who can survive in degraded land [25]. However, citrus farming is covered by dominant species of grass or above-ground vegetation as a food resource and as a protectant against predators.…”
Section: Resultsmentioning
confidence: 89%
“…Formicidae families are the most common group of insects found on agricultural and croplands. Ecosystem habitat in this research presented the former condition of that land as increasing quality, which was dominated by a predator as the Formicidae, and also the ones who can survive in degraded land [25]. However, citrus farming is covered by dominant species of grass or above-ground vegetation as a food resource and as a protectant against predators.…”
Section: Resultsmentioning
confidence: 89%
“…The results are similar with the analysis by Marja et al (2022) that landscape composition can enhance species richness and abundance of arthropods in agricultural landscapes, agroforestry was the most dominant class in almost all landscapes. Triyogo et al (2020) showed that disturbed habitats (agroforestry) have greater ant diversity. Primary and secondary forests can hold high numbers of ant species (Solar et al 2016) and increased forest area can increase ant diversity (Kuate et al 2015).…”
Section: Effect Of Habitat Condition and Landscape Composition On Ant...mentioning
confidence: 99%
“…The Formicidae family are ants that are very adaptable to new environments, including environments where human activities are present. Informed by Triyogo et al (2020) the abundance of individual ants of the Formicidae family is higher in industrial forests where human activities are present compared to natural forests. Peck, Mcquaid, and Campbell (1998) stated that Anoplolepis gracilipes are an ant species that is easy to adapt, has a very wide distribution, and can reduce the diversity of other ant species.…”
Section: The Composition Of the Family And The Number Of Insects Of Tmentioning
confidence: 99%